Graph the function y = 2x + 1.
This will be like the function y = 2x, but each y value will be 1 bigger than in that function. y is a master of one-upsmanship.
We take the graph of y = 2x and move it up by one:
Since we've moved the graph up by 1, the asymptote has moved up by 1 as well. It used an asymptote bag to move all its things.
The asymptote is now the line y = 1.
Graph the function y = -2x + 1.
This will be like the function y = -2x:
except we'll move it up by 1:
This graph looks a bit different from the others, but the shape is still the same sort of curve.
Make it rain.